Loss of autophagy protein ATG5 impairs cardiac capacity in mice and humans through diminishing mitochondrial abundance and disrupting Ca2+ cycling. Issue 6 (22nd March 2021) - Ljubojević-Holzer, Senka; Kraler, Simon; Djalinac, Nataša; Abdellatif, Mahmoud; Voglhuber, Julia; Schipke, Julia; Schmidt, Marlene; Kling, Katharina-Maria; Franke, Greta Therese; Herbst, Viktoria; Zirlik, Andreas; von Lewinski, Dirk; et al.
Abstract: Aims: Autophagy protects against the development of cardiac hypertrophy and failure. While aberrant Ca 2+ handling promotes myocardial remodelling and contributes to contractile dysfunction, the role of autophagy in maintaining Ca 2+ homeostasis remains elusive. Here, we examined whether Atg5 deficiency-mediated autophagy promotes early changes in subcellular Ca 2+ handling in ventricular cardiomyocytes, and whether those alterations associate with compromised cardiac reserve capacity, which commonly precedes the onset of heart failure. Methods and results: RT–qPCR and immunoblotting demonstrated reduced Atg5 gene and protein expression and decreased abundancy of autophagy markers in hypertrophied and failing human hearts. The function of ATG5 was examined using cardiomyocyte-specific Atg5 -knockout mice ( Atg5 −/− ). Before manifesting cardiac dysfunction, Atg5 −/− mice showed compromised cardiac reserve in response to β-adrenergic stimulation. Consequently, effort intolerance and maximal oxygen consumption were reduced during treadmill-based exercise tolerance testing. Mechanistically, cellular imaging revealed that Atg5 deprivation did not alter spatial and functional organization of intracellular Ca 2+ stores or affect Ca 2+ cycling in response to slow pacing or upon acute isoprenaline administration. However, high-frequency stimulation exposed stunted amplitude of Ca 2+ transients, augmented nucleoplasmic Ca 2+ load, and increased CaMKII activity, especially in the nuclear region of hypertrophied Atg5 −/− cardiomyocytes. These changes in Ca 2+ cycling were recapitulated in hypertrophied human cardiomyocytes. Finally, ultrastructural analysis revealed accumulation of mitochondria with reduced volume and size distribution, meanwhile functional measurements showed impaired redox balance in Atg5 −/− cardiomyocytes, implying energetic unsustainability due to overcompensation of single mitochondria, particularly under increased workload. Conclusion: Loss of cardiac Atg5 -dependent autophagy reduces mitochondrial abundance and causes subtle alterations in subcellular Ca 2+ cycling upon increased workload in mice. Autophagy-related impairment of Ca 2+ handling is progressively worsened by β-adrenergic signalling in ventricular cardiomyocytes, thereby leading to energetic exhaustion and compromised cardiac reserve. Graphical Abstract: